Lifting the lid on perioperative goal-directed therapy. (October 2021) - Martin, Daniel S.
Summary: The complex cellular interactions that underlie pathologies related to reduced oxygen delivery after surgery are poorly defined and difficult to measure. Heywood and colleagues explored the patterns of protein expression in skin biopsies taken from a subgroup of patients enrolled in a randomised trial designed to evaluate perioperative goal-directed therapy. One of their key findings was that a failure of participants to maintain preoperative systemic oxygen delivery was associated with an upregulation of intracellular proteins involved in counteracting oxidative stress. Their study highlights the importance of oxidative stress in the perioperative setting and suggests that maintenance of baseline oxygen delivery might be an important regulator of redox balance.